Encouraging primary care research: evaluation of a one-year, doctoral clinical epidemiology research course. (2nd January 2016) - Liira, Helena; Koskela, Tuomas; Thulesius, Hans; Pitkälä, Kaisu
Abstract: Objective: Research and PhDs are relatively rare in family medicine and primary care. To promote research, regular one-year research courses for primary care professionals with a focus on clinical epidemiology were started. This study explores the academic outcomes of the first four cohorts of research courses and surveys the participants' perspectives on the research course.Design: An electronic survey was sent to the research course participants. All peer-reviewed scientific papers published by these students were retrieved by literature searches in PubMed.Setting: Primary care in Finland.Subjects: A total of 46 research course participants who had finished the research courses between 2007 and 2012.Results: Of the 46 participants 29 were physicians, eight nurses, three dentists, four physiotherapists, and two nutritionists. By the end of 2014, 28 of the 46 participants (61%) had published 79 papers indexed in PubMed and seven students (15%) had completed a PhD. The participants stated that the course taught them critical thinking, and provided basic research knowledge, inspiration, and fruitful networks for research.Conclusion: A one-year, multi-professional, clinical epidemiology based research course appeared to be successful in encouraging primary care research as measured by research publications and networking. Activating teaching methods, encouraging focus on own research planning, and support from peers and tutors helped the participants to embark on research projects that resulted in PhDs for 15% of the participants. Key Points: Clinical research and PhDs are rare in primary care in Finland, which has consequences for the development of the discipline and for the availability of clinical lecturers at the universities. A clinical epidemiology oriented, one-year research course increased the activity in primary care research. Focus on own research planning and learning the challenges of research with peers appeared to enhance the success of a doctoral research course. A doctoral research course encouraged networking, and the course collaboration sometimes led to paper co-authoring. In the Nordic countries, the primary care health professionals are used to working in multi-professional teams. A multi-professional strategy also seems fruitful in doctoral research education.